Differences in sensitivity to the specific protein kinase C inhibitor Ro31-8220 between small and large bronchioles of the rat. - Chopra, L C (1994)
1. The involvement of protein kinase C (PKC) in constriction of small bronchioles has never been investigated. In this study we have examined the effects of the specific PKC inhibitors Ro31-8220 and Ro31-7549 and the non-specific inhibitor H7 on carbachol-, 5-hydroxytryptamine (5-HT)- and 4 beta-phorbol dibutyrate (4 beta-PDBu)-induced contractions in large and small bronchioles. 2. The study was performed on isolated bronchioles of the rat with internal diameters of 574 microns +/- 11 (small, n = 128), and 1475 microns +/- 32 (large, n = 93), using a Mulvaney-Halpen small vessel myograph. 3. In these preparations 4 beta-PDBu had no effect if added on its own. However, after precontracting with 30 mM K+, 0.5 microM 4 beta-PDBu caused a contractile response of 110.4 +/- 7.0% TK (TK = maximum response to 75 mM K+ in small and 69.3 +/- 6.5% TK in large bronchioles. Ro31-8220, Ro31-7549 and H7 all showed concentration-dependent inhibition of this response. 4. In small bronchioles 10 microM Ro31-8220 shifted both the carbachol and 5-HT concentration-response curves to the right, and reduced the maximum response. In contrast, 10 microM Ro31-8220 had no significant effect on the EC50 to carbachol of larger bronchioles, although the maximum response was reduced, and had no significant effect on the 5-HT concentration-response curve. 200 microM H7 shifted the carbachol concentration--response curve to the right as well as reducing the maximal response in both small and large bronchioles.(ABSTRACT TRUNCATED AT 250 WORDS)